2010
DOI: 10.1038/bmt.2010.7
|View full text |Cite
|
Sign up to set email alerts
|

Quality rather than quantity: the cord blood bank dilemma

Abstract: Growing inventories of cord blood units have facilitated access to umbilical cord cell transplantation for many patients lacking conventional stem cell donors. They are in principle 'off-the-shelf', 'fit-for-use', as well as safe and effective therapy products. Cellular enumeration is used as a surrogate of graft potency, and users rely on the rigorous assessment carried out in banks to avoid poor engraftment after thawing (loss of cells or poor function), when the patient's situation is critical. However, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 54 publications
5
76
0
9
Order By: Relevance
“…18 Querol et al have similarly reported variable quality between units. 20 This raises the possibility that part of the benefit of double-unit CBT is that, by transplanting 2 units, we increase the chance that at least 1 unit of good quality, and thus engraftment potential, is infused. Further, given that unit quality is one of the most important considerations in CBT today, the field must determine how unit quality can be reliably measured and ensured, and how poor quality units are to be investigated and/or eliminated.…”
Section: Bank Of Originmentioning
confidence: 99%
“…18 Querol et al have similarly reported variable quality between units. 20 This raises the possibility that part of the benefit of double-unit CBT is that, by transplanting 2 units, we increase the chance that at least 1 unit of good quality, and thus engraftment potential, is infused. Further, given that unit quality is one of the most important considerations in CBT today, the field must determine how unit quality can be reliably measured and ensured, and how poor quality units are to be investigated and/or eliminated.…”
Section: Bank Of Originmentioning
confidence: 99%
“…However, this selection is not possible as prefreeze CD34 ϩ cell and CFU measurements are not standardized between banks, may not reflect post-thaw results, and CD34 ϩ cell and CFU dose estimates from test vials or segments are not usually available. 33,34 Therefore, currently, TNC dose remains the only practical surrogate measurement for progenitor cell dose. Although we have demonstrated that the total TNC of the graft is strongly associated with engraftment success, our data show that the cell dose of each unit is also equally important because a dominant unit with a low TNC, CD34 ϩ cell, and CFU dose poses the risk of delayed or failed engraftment.…”
Section: Dose and Hla Match In Double-unit Cb Engraftment 3283mentioning
confidence: 99%
“…5 Although long-term preservation of cord blood was shown to not influence hematopoietic reconstitution potential in the mouse model, 6,7 it is unclear whether preservation length has an impact on hematologic recovery following CBT in humans. The fact that not all banks have adopted international guidelines, 4 such as NetCord-FACT International Standards, 8 raises an additional issue, the potential difference among banks in quality control, which might result in impairment of reconstitution potential during a prolonged period of cryopreservation or international shipment. Moreover, incomplete standardization of the processing method for cord blood 9 provokes questions about whether bank-provided information such as number of CD34 + cells reflects clinical outcomes after CBT.…”
Section: Introductionmentioning
confidence: 99%
“…As the history of the cord blood banking system becomes longer, the number of cord blood units that are cryopreserved for years has increased. 4 Global expansion of this banking has resulted in active international exchange of CBUs; 440% of CBUs are shipped beyond country borders. 5 Although long-term preservation of cord blood was shown to not influence hematopoietic reconstitution potential in the mouse model, 6,7 it is unclear whether preservation length has an impact on hematologic recovery following CBT in humans.…”
Section: Introductionmentioning
confidence: 99%